ALASAN MAHASISWA PRAKTIK PENGALAMAN LAPANGAN (PPL) BELUM MENGUASAI KETERAMPILAN DASAR MENGAJAR - Nuristiqamah Awaliyahputri B; St. Syamsudduha; M. Shabir U. (Idaarah: Jurnal Manajemen Pendidikan, 2019)
Field Experience Practices (PPL) in schools is carried out so that students train themselves before becoming real educators. However, what happens in the field is actually a lot of things that make students not maximal in mastering basic teaching skills. The data was obtained through observation and interviews with students. Some of the problems faced by PPL students are from themselves because they lack training and lack of confidence; student not ready to learn, do not ignore the arrival of students, late in class, do other activities, feel bored, and out of class when learning takes place; the time of learning that is not well controlled, subject is not mastered, as well as inadequate learning tools and media. Based on the problems they faced, students should be given special guidance with controlled exercises or microteaching, so that students can reduce errors that can occur when directly involved in the field.